World revolution, 1917-1936 : the rise and fall of the Communist International - James, C. L. R. (Cyril Lionel Robert), 1901-1989 (C.L.R. James Archives (Series), 2017)
Originally published in 1937, C.L.R. James's World Revolution is a pioneering Marxist analysis of the history of revolutions during the interwar period and of the fundamental conflict between Trotsky and Stalin. James, who was a leading Trotskyist activist in Britain, outlines Russia's transition from Communist revolution to a Stalinist totalitarian state bureaucracy. He also provides an account of the ideological contestations within the Communist International while examining its influence on the development of the Soviet Union and its changing role in revolutions in Spain, China, Germany, and Central Europe. Published to commemorate the centenary of the Russian Revolution, this definitive edition of World Revolution features a new introduction by Christian Hogsbjerg and includes rare archival material, selected contemporary reviews, and extracts from James's 1939 interview with Trotsky.